Effect of the addition of lysophospholipids in the diet on productive parameters in broilers COBB 500 - Hurtado, Ernesto Antonio (2022)
In recent times, the use of lysophospholipids (LFL) in the poultry industry has become relevant due to their emulsifying action. For this reason, an experiment was carried out to evaluate the LFL incorporated in the diet of COBB 500 chickens in three growth phases on the productive response. The LFL source used was the one contained in Lipidol®. A total of 288 chickens aged 1-42 days were used in a completely randomized design with a 4x3 factorial arrangement, with factor A being four levels of Lipidol (0, 0.50, 0.75, 1.0 kg/t of feed) and factor B being three periods of use (1-7; 1-15, 1-21 days). Accumulated weekly weight (AWW), daily weight gain (DWG), weekly feed consumption (WFC) and feed conversion (FC) were evaluated. The inclusion levels and periods of use (PU) of the LFLs improved AWW, DWG and WFC (p<0.01); however, PUs did not affect FC. It is concluded that the productive parameters of COBB 500 chickens improve with levels between 0.75 and 1.0 kg/t of feed, except for FC.